Application of a LED-UV based light technology for decontamination of chicken breast fillets: Impact on microbiota and quality attributes. (June 2021) - Soro, Arturo B.; Whyte, Paul; Bolton, Declan J.; Tiwari, Brijesh K.
Abstract: Light-emitting diode (LED) technologies are economical and efficient devices that could be considered in poultry processing as disinfection strategies. This study evaluated the efficacy of a LED-based device to reduce the microbial load on chicken meat and investigated it's impact on selected quality parameters. Quality parameters including pH, texture and color after LED-UV exposure and during subsequent storage for 7 days at 4 ̊C were investigated. Diced chicken breast fillets were exposed to UV light wavelengths of 255, 280, 300 and 365 nm for 2, 4, 6, 8 and 10 min. A microbiological analysis was conducted on chicken samples to enumerate bacterial counts. Reductions between 1.17 and 1.67 log CFU/g for total viable counts of mesophilic, psychrophilic bacteria and total Enterobacteriaceae counts were observed, whereas, up to 2 log CFU/g was obtained for Pseudomonas and lactic acid bacteria groups after treatment with wavelengths of 280, 300 and 365 nm. Furthermore, color, texture and pH were not affected by exposure to UV light at 280 nm even following 7 days storage. Thus, LED-based technologies could be applied on poultry meat to reduce the levels of spoilage bacteria while maintaining quality attributes. Graphical abstract: Image 1 Highlights: Wavelengths of 280, 300 and 365 nm obtained the best inactivation results. The most affected bacteria were the Pseudomonas genus and lactic acid bacteria. Application of UV light at 280 min and storage did not alter pH, color and texture. LED-UV based technology is a potential disinfection strategy of chicken fillets.